Prevalence and category of Anemia with Assessment of clinical parameters - Garg, Ashok Kumar (International Journal of Psychosocial Rehabilitation, 2009)
Introduction: The prevalence of anemia is much higher and has far reaching consequences, especially the severe degrees of anemia. We evaluate the hematological parameters and categorization of anemia in adults in a tertiary care hospital. Materials and Methods: Cases were selected according to criteria mentioned above. Also, detailed history taking and clinical examination was done. This was followed by investigations. Result: We studied 115 cases which showed low hemoglobin percentage in automated blood cell counter. Out of 115 cases 84(73.04%) were female and 31(26.95%) were males. Conclusion: The utility of hematological parameters obtained from automated cell counters aids in increased diagnostic accuracy. In the present study, there was predominance of anemia in 2nd decade among females and microcytic hypochromic type was common.